Implementing a gamified web application for educating parents on the dangers of social media towards children - Tanskanen, Tuomas (My University, 2022)
Social networking is reported to be one of the most popular digital activities in the world. In 2020, over 3.6 billion people were using social media worldwide. The increasing usage of mobile devices has contributed into the growth of social networking sites such as Instagram, Twitter and YouTube. Children who use social media can become the targets of bullying which can have negative consequences for their well-being. Parents should know about this and other harmful aspects of social media towards children. The purpose of this thesis is to investigate the development process of a gamified web application for educating parents on the dangers of social media towards children. The empirical research was conducted by providing a questionnaire for the parents on the developed web application. The questionnaire's purpose was to gather qualitative information from the parents about the web application and its usability. The literature review of this thesis consists mainly of articles and conference papers. Theoretical material was gathered from literature on the use of gamification in education and social media usage and its affect on school children. The results of this thesis indicate that a gamified web application could be a useful tool for educating the parents of the dangers of social towards children. The application teaches the parents that they should watch closely how their child is using social media in order to ensure that they are doing it safely.

Sosiaalinen media on yksi suosituimmista digitaalisista aktiviteeteista maailmalla. Vuonna 2020, yli 3,6 miljardia ihmistä maailmassa käytti sosiaalista mediaa. Mobiililaitteiden käytön lisääntyminen on kasvattanut sosiaalisen median palvelujen kuten Instagramin, Twitterin sekä YouTuben käyttäjien määrää. Lapsista voi tulla kiusaamisen kohteita sosiaalisessa mediassa, millä voi olla negatiivisia vaikutuksia heidän hyvinvointiinsa. Lasten vanhempien pitäisi tietää kuinka sosiaalisen median käyttö voi olla haitallista lapsille. Tämän diplomityön tavoitteena on tutkia pelillistetyn web-sovelluksen kehitysprosessia. Web-sovelluksen tarkoituksena on opettaa vanhemmille lasten sosiaalisessa mediassa kohtaamista vaaroista. Tutkimuksen empiirinen osuus koostuu kehitettyyn web-sovellukseen liittyvästä kyselylomakkeesta johon vanhemmat vastasivat testattuaan sovellusta. Tutkimuskyselyn tavoitteena oli kerätä vanhemmilta laadullista tietoa web-sovelluksesta sekä sen käytettävyydestä. Tutkimuksen teoriaosuus koostuu enimmäkseen artikkeleista sekä konferenssijulkaisuista. Työn teoreettinen materiaali on kerätty kirjallisuudesta, joka käsittelee pelillistämisen hyödyntämistä opetuksessa sekä sosiaalisen median käytön aiheuttamia vaikutuksia koululapsiin. Tämän tutkielman tulos osoittaa, että pelillistetty web-sovellus voi olla kätevä työkalu, jolla voidaan opettaa vanhempia lasten sosiaalisessa mediassa kohtaamista vaaroista. Sovellus opettaa vanhempia seuraamaan tarkasti kuinka heidän lapsensa käyttää sosiaalista mediaa. Tällä tavalla he voivat varmistaa, että lapsi käyttää sosiaalista mediaa turvallisesti.
Keywords: web application, application development, gamification, social media web-sovellus, ohjelmistokehitys, pelillistäminen, sosiaalinen media